Guinea : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
The paper first discusses price trends and the relationship between money growth and inflation. Second, it focuses on the central challenge of improving competitiveness and promoting exports to enhance growth in the economy. Finally, it reviews the microfinance sector. The study also includes the following statistical data: economic and financial indicators, consumer price index, central government revenue and expenditure, monetary survey, structure of interest rates, balance of payments, composition of imports and merchandise exports, nominal and effective exchange rates, and external public debt.